Research on Demand Side Response System of Electricity Price Under Electricity Market Incentive Mechanism - Xianyu, Fu; Hongmei, Zhou; Jiang, Qi-jie Jiang; Fan, Ke (Distributed Generation & Alternative Energy Journal, 2021)
Aiming at the traditional day-ahead dispatching scheme of power generation, the paper proposes a power system security optimization dispatching model that considers the demand response of electricity prices under the electricity market incentive mechanism. Based on the peak and valley time-of-use elec- tricity price, the paper establishes an incentive compensation mechanism to encourage users to be active. Participating in demand-side resource schedul- ing makes the effect of “peak shaving and valley filling” more pronounced. Simultaneously, to rationally configure the reserve capacity of grid operation, the system incorporates the expected power outage loss into the proposed model to ensure the grid operation safety. The analysis of calculation exam- ples based on IEEE24 nodes shows that the power optimal dispatch model proposed in the paper considering demand response and expected outage loss can reduce the operating cost of the power grid under the premise of ensuring a certain level of reliability and realize the economy of the power system in the market environment and safe operation.